Pollination Best Practices in Southern Highbush Blueberry in Florida - Rachel Mallinger; Douglas A. Phillips (EDIS)
Southern highbush blueberry is the primary blueberry species grown in Florida. It is dependent upon pollinating insects for adequate pollination and fruit. Some Florida growers have reported cases of low fruit set in recent years, in particular on the cultivars Meadowlark and Emerald, which may have been due in part to poor pollination. This 5-page fact sheet written by Rachel E. Mallinger and Douglas A. Phillips and published by the UF/IFAS Department of Entomology and Nematology will discuss blueberry pollinators, some causes of poor pollination, and current best practices to reduce the possibility of poor pollination of southern highbush blueberry. http://edis.ifas.ufl.edu/in1237